BORON IN PREVENTING OF SHOOT DIEBACK ON EUCALYPTUS BENTHAMII GROWN IN SOIL WITH DIFFERENT WATER REGIMES - Rosa Dias, Luciana Patrícia; Gatiboni, Luciano Colpo; Miquelutti, Davi José; Brunetto, Gustavo; Pereira Campos, Diego Joaquim (Scientia Agraria, 2017)
The water deficit interferes in the boron (B) uptake by eucalyptus, causing shoot dieback in young plants. The objective of this study was to evaluate the occurrence of shoot dieback in Eucalyptus benthamii submitted to doses of boron and water regimes in a Humic Cambisol of the Southern Plateau of the state of Santa Catarina. The experiment was conducted in greenhouse (Lages-SC) in a completely randomized experimental design, in a 4 x 3 factorial scheme, with three replications, adding 0, 0.55, 1.1 and 2.75 g boron plant-1 in the soil, and three water regimes (60, 80 and 100% of the field capacity). The stem diameter and the plants height were measured, using a visual analysis of dieback. The dry mass and boron contents in the tissues and in the soil, were also determined. Water deficiency affected negatively dry matter but it was not affected by boron application. The highest occurrence of shoot dieback was observed in the treatments without addition of boron and in the more restrictive water regime. Fertilization with 0.55 g boron plant-1 in soil was sufficient to avoid shoot dieback.